FAKTOR-FAKTOR PENENTU MINAT KONSUMEN UNTUK MEMILIH TEMPAT LAYANAN LAUNDRY - Riyadi - Riyadi; Kurniani - Kurniani; Rusmini - Rusmini (Politeknik Negeri Semarang, 2019)
This research was conducted in the campus area of Tembalang where in the last 10 years laundry business began to be in booming. This study formulates the problem related to the dimensions of any underlying consumer interest variables and what factors can represent consumer interest variables. While the purpose of this study is to determine the dimensions underlying consumer interest variables and to determine the factors that can represent the variables of consumer interest. This research is a survey research by taking a sample of 100 respondents by using purposive sampling of a laundry customer population in the area of Tembalang. While the method of analysis used in this study is a factor analysis which is one multivariet analysis techniques that are widely used in marketing research. The results of testing instrument showed that the instrument is valid and reliable. While the SPSS processing results show that Kaiser-Meyer-Olkin value (KMO) of 0.857 exceeds the value of 0.5 which means that on the basis of this KMO test factor analysis is feasible. In this study, to determine the number of valid variables, It is used Eigenvalue value. With this criterion, a factor having an Eigenvalue of one or more 1 is considered valid. The results concluded that the dimensions underlying consumer interest variables in using laundry services identified as many as 25 components. Of the 25 components, on the basis of factor analysis extracted into 5 factors considered valid. The five factors that can represent the variables of consumer interest are interpreted as hospitallity, accuracy, guarantee, performance and convenience